Psychological Profiles and Clinical Clusters of Patients Diagnosed With Functional Neurological Disorder - Pun, Paul; Frater, Julanne; Broughton, Megan; Dob, Rian; Lehn, Alexander (Frontiers in Neurology, 2020)
Our understanding about underlying mechanisms leading to Functional Neurological Disorders (FND) has changed in recent years. While in the past these disorders were presumed to be solely due to psychological issues we know now that their development is dependent on complex interactions between biological, psychological and social factors. We present an analysis of clinical presentations and psychological profiles of patients who were seen in our FND outpatient clinic over three years. We aim to review the prevalence of common symptoms in the patients seen within our clinic, and to identify any common psychological or psychiatric profiles that differentiated these symptom groups. This may help to elucidate underlying mechanisms leading to the development of functional symptoms and identify the predisposing, triggering and perpetuation factors.